Expert System for Diagnosis of Hypertension Disease Using Web-Based Backward Chaining Method - Fadil Aulia Rahman; Iriene Putri Mulyadi; Sanjaya Alacsel (Jurnal Nasional Komputasi dan Teknologi Informasi (JNKTI), 2025)
Abstract - Seeing the rapid development of technology today, a technology system has also been developed that is able to adopt human processes and ways of thinking, namely expert systems. An expert system is a computer program built to model the problem-solving ability of an expert. In this case, the author tries to apply an expert system to detect hypertension. The main objective of this final project is to build a knowledge-based system to diagnose hypertension and what solutions should be taken to overcome hypertension which is represented in the form of a website using PHP programming with a MySQ L database, so that we can find out as early as possible whether we suffer from hypertension or not based on the selected symptoms.Keywords: Expert System, HypertensionAbstrak - Melihat perkembangan teknologi yang semakin pesat saat ini, maka dikembangkan pula sebuah sistem teknologi yang mampu mengadopsi proses dan cara berpikir manusia, yaitu sistem pakar. Sistem pakar adalah program komputer yang dibangun untuk memodelkan kemampuan pemecahan masalah seorang pakar. Dalam hal ini, penulis mencoba menerapkan sistem pakar untuk mendeteksi penyakit hipertensi. Tujuan utama dari tugas akhir ini adalah membangun sebuah sistem berbasis pengetahuan untuk mendiagnosa penyakit hipertensi dan solusi apa yang harus dilakukan untuk mengatasi penyakit hipertensi yang direpresentasikan dalam bentuk website menggunakan pemrograman PHP dengan basis data MySQL, sehingga kita dapat mengetahui sedini mungkin apakah kita menderita penyakit hipertensi atau tidak berdasarkan gejala-gejala yang dipilih.Kata kunci: Sistem Pakar, Hipertensi